Theatre stratum in Turgenev’s Clara Milich - Шелогурова, Галина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The article presents an attempt of interpretation of the last story by Turgenev from the point of view of theatre as a specific cultural and social phenomenon. This approach enables us 1) to distinguish between concepts of drama and tragedy as they are used in the text and metatext of the story; 2) to get out of the text’s boundaries and to involve biographical and historical contexts to the analysis.